Banking secrecy in Malaysia: a legal myth / Abd. Razak Said - Said, Abd. Razak (Faculty of Law, 1987)
This article intends to prove that banking secrecy in Malaysia is a legal myth, and not being greatly imphasized during every day banking practice and not being treated as sacred by the government. The discussion begins, with discussion about the practice in the Malaysian banks and the provisions of the Malaysian Banking Act 1975. Case law study too is done in order to have a better understanding of the principle. To prove the hypotheses, exceptions from the Malaysian Banking Act 1975 and also explanations from case law will be analysed. Tournier v National Provincial and Union Bank of England (1924) 1KB 461 give the best account on the principle and its exceptions. So, this case can be said as the core of this discussion* The case gives a number of qualifications and limitations tor banking secrecy and its broadness helps to prove the hypothesis. Other normal practices which deviate from the rule are looked into. To provide for a better view of the practice in Malaysia, comparisons are made with practices in countries like Switzerland, which is well known for its exercise of the principle, and also Singapore, which though basically have a similar banking law with Malaysia, has a special feature in that it has implemented the system of numbered accounts which emphasize on confidentiality. From all these facts a conclusion will be made and a discussion for its justifiability will be done.